Does the Green Great Wall effectively decrease dust storm intensity in China? A study based on NOAA NDVI and weather station data - Tan, Minghong; Li, Xiubin (Land use policy, 2015)
•DSI definition considers the frequency, visibility and duration of dust events.•Changes in NDVI did not synchronize with precipitation.•Implementation of the GGW program was observed to have improved vegetation density.•NDVI variable had a close negative relationship with DSI measurements. China launched its “Green Great Wall” (GGW) program in 1978. However, the effects of this program are subject to intense debate. This study compares changes in the vegetation index in regions where the GGW program has been implemented with those where it has not. Subsequently, a definition to measure dust storm intensity (DSI) was proposed that better calculates the intensity of dust events; it considers the frequency, visibility, and duration of dust events. The results show that in the GGW region, vegetation has greatly improved, while it varied dramatically outside the GGW region. In the mid-1980s, DSI decreased significantly, different from the changes in dust storm frequency in the study region. By discounting the effects of climatic change and human pressures, the results show that the GGW program greatly improved the vegetation index and effectively reduced DSI in northern China.